Developing self-efficacy, mattering, and general well-being through community-based education in the rural area - Abdul Aziz; Mohammad Padil; Mujtahid Mujtahid; Kususanto Ditto Prihadi (International Journal of Evaluation and Research in Education (IJERE), 2022)
This qualitative study aimed to explore the implementation of community-based education (CBE) in the village of Desa Karang Pandan, Malang, East Java, Indonesia. The CBE was conducted in order to educate the community members in information technology, Arabic language, Quran reading, Boyscout activities, and indigenous martial arts. Apart from that, the CBE was implemented to address specific communal issues, such as lack of self-efficacy, sense of mattering, and general well-being of the community members. Data was collected through observations and interviews along the CBE program, and analyzed by utilizing thematic analysis methods. Positive responses were shown in the interview results. They were represented by the frequent occurrences of themes such as improvement of mattering and self-efficacy, higher motivation to learn and the development of general well-being. Nevertheless, it is possible that the positive responses from the community members were caused by the novelty effect of the program. Further concerns and limitations are discussed in the end of this paper.